Developmental role of acetylcholinesterase in impulse control in zebrafish - Parker, Matthew O.; Brock, Alistair J.; Sudwarts, Ari; Teh, Muy-Teck; Combe, Fraser J.; Brennan, Caroline H. (Frontiers in Behavioral Neuroscience, 2015)
Cellular and molecular processes that mediate individual variability in impulsivity, a key behavioural component of many neuropsychiatric disorders, are poorly understood. Zebrafish heterozygous for a nonsense mutation in Ache (achesb55/+) showed lower levels of impulsivity in a 5-choice serial reaction time task (5-CSRTT) than wild type and ache+/+. Assessment of expression of cholinergic (nAChR), serotonergic (5-HT) and dopamine (DR) receptor mRNA in both adult and larval (9dpf) achesb55/+ revealed significant downregulation of Chrna2, Chrna5 and Drd2 mRNA in achesb55/+ larvae, but no differences in adults. Acute exposure to cholinergic agonist/antagonists had no effect on impulsivity, supporting the hypothesis that behavioural effects observed in adults were due to lasting impact of developmental alterations in cholinergic and dopaminergic signalling. This shows the cross-species role of cholinergic signalling during brain development in impulsivity, and suggests zebrafish may be a useful model for the role of cholinergic pathways as a target for therapeutic advances in addiction medicine.